GEOMECHANICAL MODELS AND IONOSPHERIC VARIATIONS RELATED TO STRONGEST EARTHQUAKES AND WEAK INFLUENCE OF ATMOSPHERIC PRESSURE GRADIENTS - Bondur V.G.; Garagash I.A.; Gokhberg M.B.; Lapshin V.M.; Nechaev Y.V.; Steblov G.M.; Shalimov S.L. (My University, 2007)
he influence of large-scale gradients of the atmospheric pressure on the preparation of some strong earthquakes including the earthquake in Sumatra on December 26, 2004, with a magnitude of M ~ 9.0 was studied on the basis of detailed geomechanical models of the Earth’s crust and data obtained using satellite navigation systems.